2002
DOI: 10.2355/isijinternational.42.1399
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Analysis of Pitting Corrosion in Artificial Crevice of Stainless Steel by X-ray Absorption Fine Structure.

Abstract: A new technique by XAFS (X-ray Absorption Fine Structures) and XANES (X-ray Absorption Near Edge Structures) has been developed for in situ observation of metal corrosion. XAFS and XANES spectra were obtained with a special electrochemical cell to elucidate pitting for stainless steel. A sheet of stainless steel was attached below a reservoir of a specific aqueous environment with thin films. The solution in the reservoir attached to the metal thorough the film, and the solution inside the film corresponds to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…Whereas the structures near the interface showed a siginificanto difference near the corroding interface; in LiCl, Mo-O bonding similar to MoO 6 octahedra in MoO 3 oxide or MoO 4 2Ϫ ions was dominant, but in LiBr, the Mo-O-Br complex formed. 18,19) Sugimoto et al analyzed state of Mo on stainless steels in hydrochloric solutions and Mo was considered to exist in passive film improving corrosion resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the structures near the interface showed a siginificanto difference near the corroding interface; in LiCl, Mo-O bonding similar to MoO 6 octahedra in MoO 3 oxide or MoO 4 2Ϫ ions was dominant, but in LiBr, the Mo-O-Br complex formed. 18,19) Sugimoto et al analyzed state of Mo on stainless steels in hydrochloric solutions and Mo was considered to exist in passive film improving corrosion resistance.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that Mo improves the pitting corrosion resistance of stainless steels. 13) This has been mainly attributed to the existence of Mo-species in passive films, 2,49) and to the inhibition effect of the dissolved Mospecies. 1014) For instance, Montemor et al proposed that Mo exists as Mo(IV), Mo(VI), and/or metallic Mo in the oxide films on stainless steels.…”
Section: Introductionmentioning
confidence: 99%
“…4) Kimura et al demonstrated that the formation of MoO 4 2¹ networks near the dissolving metal interface enhances the pitting corrosion resistance of stainless steel. 13) There is no unified theory about the role of Mo.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, alloyed molybdenum provides much less extra resistance to pitting corrosion in bromide solutions than in chloride solutions. 1 The reason for this behavior was sought by Kimura et al 2 using X-ray absorption spectroscopy performed in situ in 1 M solutions of LiCl and LiBr on artificial "crevice" electrodes made from metal foil mounted in resin ͑since these had one-dimensional transport they were really more like artificial pits͒. The potential used was fairly oxidizing, 0.8 V vs Ag/AgCl, but not unreasonably so.…”
mentioning
confidence: 97%